2017
DOI: 10.1016/j.jtcvs.2017.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic parameters predict adverse outcomes following biventricular conversion with single-ventricle palliation takedown

Abstract: Elevated preoperative LVEDP is a risk factor for suboptimal postoperative hemodynamic parameters and adverse outcome following BiV conversion from single-ventricle palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…We decided to proceed with conversion to biventricular circulation despite an elevated LVEDP of 14 mm Hg. Patients with LVEDP ≥ 13 mm Hg have been shown to carry a high risk of unfavourable outcome after biventricular conversion 7 . Looking at the data retrospectively, staying with univentricular circulation and replacing the TCPC conduit to remove inter‐atrial obstruction would seem as a more secure choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We decided to proceed with conversion to biventricular circulation despite an elevated LVEDP of 14 mm Hg. Patients with LVEDP ≥ 13 mm Hg have been shown to carry a high risk of unfavourable outcome after biventricular conversion 7 . Looking at the data retrospectively, staying with univentricular circulation and replacing the TCPC conduit to remove inter‐atrial obstruction would seem as a more secure choice.…”
Section: Discussionmentioning
confidence: 99%
“…The decision is usually made during newborn age, but conversion to biventricular is possible later if the LV grows enough. 7 In our patient, after an initial aortic valvuloplasty, univentricular circulation was chosen. Various LV scores calculated retrospectively would favour the same decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it may be interesting to identify the hemodynamic conditions preserving the potential for growth of the LV. 6,7 In the first case, LV postcharge was improved by coarctation repair, and thereafter the removal of the supravalvular membrane associated with the spontaneous restriction of the ventricular septal defect might have improved LV preload. But the MV and LV growth was slow and considered poor at 1 year of age before the Kawashima intervention.…”
Section: Commentmentioning
confidence: 99%
“…The Boston group has championed left ventricle recruitment and biventricular conversion strategies and has contributed a great deal to our knowledge related to this matter. [1][2][3] They introduced staged left ventricular recruitment to progressively increase left ventricle loading and they demonstrated subsequent growth allowing successful biventricular conversion. 1,2 They also demonstrated that although growth in size was necessary, it was not always enough for predicting successful biventricular conversion and that diastolic dysfunction was a major problem in some of those patients.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 99%